A revision of Aleurodicus Douglas (Sternorrhyncha, Aleyrodidae), with two new genera proposed for palaeotropical natives and an identification guide to world genera of Aleurodicinae - Martin, Jon H. (Zootaxa, 2008)
The genus Aleurodicus is discussed in the context of the whole subfamily Aleurodicinae, and is fully revised with 35 species now included, 10 of them newly described here. The genus Lecanoideus Quaintance & Baker is here regarded as a junior synonym of Aleurodicus syn. nov., and Aleurodicus fucatus Bondar is proposed as a junior synonym of A. capiangae Bondar syn. nov.. Palaealeurodicus gen. nov. is described to accommodate six native Asian species hitherto included in Aleurodicus, along with one new species here described. Aleuroctarthrus gen. nov. is proposed to accommodate Aleurodicus destructor Mackie. Two species are here transferred from Aleurodicus to other genera. Puparial keys are provided to the worldwide genera of Aleurodicinae, and to the described species of Aleurodicus and Palaealeurodicus. Lectotypes are here designated for 11 species of Aleurodicinae, and a neotype for one species. A check list is provided to all the species treated in this paper. The paper is illustrated with 144 figures including 7 plates of habitus photographs.